You don’t know what you don’t know: Insights into new graduate nurse transition to practice in rural emergency departments - Moon, Elizabeth M.; Rohatinsky, Noelle; Penz, Kelly (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence)

(untitled) (Meadowlight Media, 2026)
Background: Rural emergency departments (EDs) across Canada are increasingly reliant on new graduate nurses (NGNs) to maintain services, despite a longstanding belief that emergency practice is unsuitable for novice clinicians. While NGN transition has been widely studied in both rural and emergency contexts, little is known about how these challenges interact in rural EDs. Understanding NGNs’ experiences in this high-acuity, resource-limited setting is essential to supporting safe, sustainable workforce development.Methods: This qualitative study used narrative inquiry to explore the experiences of three NGNs who worked in rural Albertan EDs during their first year of practice. Data were co-created through a series of in-depth, conversational interviews and analyzed through an iterative process of narrative construction and cross-narrative thematic analysis. Guided by Clandinin and Connelly’s three-dimensional narrative space (temporality, sociality, and place), the analysis focused on how NGNs experienced transition over time, in context, and through relationships.Results: Four resonant threads were identified across participant narratives: peer and team relationships, learning on the job, becoming a rural emergency nurse, and developing confidence. Despite minimal orientation or formal education, participants generally described positive transitions, supported by strong collegial relationships, informal mentorship, and collaborative nurse-physician dynamics. Self-directed learning and experiential growth were central to their development. However, even isolated instances of exclusion, hierarchy, or poor leadership had a lasting negative impact on confidence and well-being.Conclusions: These findings challenge assumptions that formal transition programs are always necessary, highlighting the power of informal peer support and team culture in shaping NGN experiences. Leaders and educators in rural EDs can enhance transition outcomes by fostering inclusive team environments, supporting interprofessional collaboration, and offering timely, context-specific learning opportunities that build both competence and confidence.